2023
DOI: 10.2147/jaa.s405943
|View full text |Cite
|
Sign up to set email alerts
|

Can Pharmacists’ Counseling Improve the Use of Inhalers and Quality of Life? A Prospective “Pre” and “Post” Education Analysis in Mardan, Pakistan

Abstract: Introduction Asthma is one of the common major non-communicable respiratory diseases, and is associated with a lower health-related quality of life (QOL). Poor inhalation is a significant contributing factor to poor control of asthma. Community pharmacist has a vital role to play in assisting patients and ultimately improving their asthma conditions through the use of inhalers. Aim This study aimed to assess the effectiveness of “pre” and “post” educational intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 42 publications
0
0
0
Order By: Relevance
“…This information is particularly relevant when considering the potential impact on patients' lives. Gul et al [ 12 ], in a 2023 article, not only demonstrated a statistically significant improvement in the inhalation technique of patients instructed by pharmacists but also an improvement in their quality of life. In another study, Basheti et al quantified this improvement by assessing forced expiratory volume in 1 second (FEV1) and the use of rescue medication in rural areas of Jordan [ 13 ], finding that patients instructed by pharmacists had statistically superior results in spirometry and symptom assessment checklists.…”
Section: Discussionmentioning
confidence: 99%
“…This information is particularly relevant when considering the potential impact on patients' lives. Gul et al [ 12 ], in a 2023 article, not only demonstrated a statistically significant improvement in the inhalation technique of patients instructed by pharmacists but also an improvement in their quality of life. In another study, Basheti et al quantified this improvement by assessing forced expiratory volume in 1 second (FEV1) and the use of rescue medication in rural areas of Jordan [ 13 ], finding that patients instructed by pharmacists had statistically superior results in spirometry and symptom assessment checklists.…”
Section: Discussionmentioning
confidence: 99%